74.1k views
5 votes
Evaluate the function.


f(x) = - x^(2) - 7x - 5
Find

f( - 5)


User Belma
by
4.9k points

1 Answer

3 votes

Answer: 5

===================================================

Step-by-step explanation:

Everywhere you see an x, replace it with -5. Then use the order of operations PEMDAS to simplify


f(x) = -x^2 - 7x - 5\\\\f(-5) = -(-5)^2 - 7(-5) - 5\\\\f(-5) = -(25) - 7(-5) - 5\\\\f(-5) = -25 + 35 - 5\\\\f(-5) = 10 - 5\\\\f(-5) = 5\\\\

Keep in mind that for the x^2 term, you are squaring all of x = -5, which includes the negative as well. So that means

x^2 = (-5)^2 = (-5)*(-5) = 25

but sticking a negative out front makes

-x^2 = -(-5)^2 = -25

User Czheo
by
5.7k points